Systematic review and meta-analysis of omalizumab for IgE-mediated food allergy in children and young adults - Zhang, Ya; Liang, Bin; Tian, Liang; Chen, Bin; Wu, Shanshan (Frontiers in Immunology, 2025)
ObjectivesThis meta-analysis aims to evaluate the efficacy of omalizumab (as monotherapy or combined with OIT) in achieving target maintenance dose (TMD), and its safety profile in terms of treatment-emergent adverse events (TEAEs) and epinephrine use, in children and young adults with IgE-mediated food allergy.MethodsA comprehensive literature search was conducted across PubMed, Embase, Cochrane Library, and Web of Science databases to identify relevant randomized controlled trials (RCTs) and controlled clinical trials (CCTs). Eligible studies compared omalizumab-based interventions (monotherapy or OIT combination) with control strategies (placebo, placebo plus OIT, or strict allergen avoidance) in children and adolescents with IgE-mediated food allergy. The primary efficacy endpoint was the achievement of a target maintenance dose (TMD), defined as the maximum allergen dose tolerated without dose-limiting symptoms. Safety outcomes included the incidence of treatment-emergent adverse events (TEAEs) and the requirement for epinephrine administration. Data synthesis employed random-effects models to calculate pooled risk ratios (RRs) with 95% confidence intervals (CIs).ResultsEight studies (n = 734 participants) met the inclusion criteria, comprising 7 RCTs and 1 CCT. Pooled analysis demonstrated that omalizumab-based therapy significantly increased the likelihood of achieving a clinically meaningful TMD compared to control interventions (RR = 3.07, 95% CI: 1.42–6.62; p < 0.001), with consistent efficacy observed across subgroups of multiple food allergies, peanut allergy. With respect to safety, no statistically significant difference was noted in the overall incidence of TEAEs between the omalizumab and control groups (RR = 1.02, 95% CI: 0.74–1.41; p = 0.889). Similarly, the rate of epinephrine use during oral food challenges or treatment did not differ significantly between groups (RR = 0.59, 95% CI: 0.07–4.78; p = 0.099), though the wide confidence intervals indicate substantial uncertainty due to limited data.ConclusionThis meta-analysis provides robust evidence that omalizumab, either as monotherapy or in combination with OIT, significantly enhances allergen tolerance in children and young adults with IgE-mediated food allergy. Importantly, this therapeutic benefit is not accompanied by a significant increase in the overall burden of adverse events or epinephrine use relative to control strategies. Omalizumab thus represents a valuable therapeutic option for improving desensitization outcomes in this vulnerable population.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251087191.